Understanding the investor : a Maltese study of risk and behavior in financial investment decisions - Bonello, Antonietta (Emerald Publishing, 2019)
In finance, understanding investors and their motivations is key for any business and policy-maker. Understanding the Investor: A Maltese Study of Risk and Behavior in Financial Investment Decisionsoffers a nuanced view of the Maltese investor and the Malta Stock Exchange, and its implications on the wider financial world.